Review of the Implementation of the Criminal Justice Process in Sexual Violence Cases: Case Studies in District Courts - Yusep Mulyana; Sitti Rosmini; Andi Cakra Cindrapole; Zuraidah Zuraidah; Ridwan Fauzy Lestahulu (Rechtsnormen: Journal of Law, 2024)
Background. The background research on the review of the criminal justice process in cases of sexual violence is highly relevant as these cases often cause controversy and concern in society. These cases not only damage individuals physically and psychologically, but also make people distrust the justice system. It is imperative to evaluate how the criminal justice process is carried out in dealing with sexual violence cases in the District Court, where such cases are processed. Purpose. This study aims to evaluate the effectiveness and efficiency of the criminal justice process in cases of sexual violence in the District Court. This case study also identifies key stages in handling sexual violence cases, from investigation to final decision. An additional objective of this study was to discover obstacles that may be encountered in the implementation of the criminal justice process. Method. Qualitative field research is used. Data will be collected through direct observation of the criminal justice process in sexual violence cases at the District Court, interviews with judges, prosecutors, lawyers, and other parties related to the case, and analysis of documents relating to sexual violence cases that have been processed. Results. The research shows that despite efforts to improve the criminal justice process in sexual violence cases at the District Court, there are several issues that need to be addressed. The results showed that some cases were delayed, there was a lack of support for victims, and sometimes disagreements between the law enforcement agencies involved. However, it was also found that positive progress has been made to improve the efficiency and effectiveness of the criminal justice process in sexual violence cases. Conclusion. This research found that, although there are obstacles and barriers in carrying out the criminal justice process in sexual violence cases in the District Court, there is still room for improvement and reform. To ensure justice for all parties involved in sexual violence cases, better collaboration between relevant institutions, better support for victims, and strengthening of legal procedures are needed.